A preliminary design method for axisymmetric turbomachinery disks based on topology optimization. (April 2022) - Wang, Bo; Wang, Guangming; Tian, Kuo; Shi, Yunfeng; Zhou, Caihua; Liu, Heng; Xu, Shengli
The topology optimization can be used to obtain preliminary turbomachinery disk designs which meet strength requirement. In order to eliminate enclosed holes which challenge manufacturing processes and to ensure distinct solid-void interface in the optimal result obtained by the topology optimization, a density distribution function is introduced for each element column in the design domain. Then, a parameter in each function is used to determine the disk's thickness at corresponding radial position by controlling element densities. Once thicknesses at all radial positions are optimized, the shape of disk is thus determined. In this way, the optimization problem can be simplified by using these parameters as design variables. Illustrative examples are carried out to demonstrate the effectiveness of the proposed method in designing both compressor disks and turbine disks in comparison to the software T-Axis Disk and shape optimization method.